Reference Values for Continuous Glucose Monitoring in Chinese Subjects - Zhou, Jian; Li, Hong; Ran, Xingwu; Yang, Wenying; Li, Qiang; Peng, Yongde; Li, Yanbing; Gao, Xin; Luan, Xiaojun; Wang, Weiqing; Jia, Weiping (Diabetes care, 2009)
OBJECTIVE: The widespread clinical application of continuous glucose monitoring (CGM) is limited by the lack of generally accepted reference values. This multicenter study aims to establish preliminary normal reference values for CGM parameters in a sample of healthy Chinese subjects. RESEARCH DESIGN AND METHODS: A total of 434 healthy individuals with normal glucose regulation completed a 3-day period of glucose monitoring using a CGM system. The 24-h mean blood glucose (24-h MBG) and the percentage of time that subjects' blood glucose levels were greater-than-or-equal140 mg/dl (PT140) and [less-than or equal to]70 mg/dl (PT70) within 24 h were analyzed. RESULTS: There was excellent compliance of finger stick blood glucose values with CGM measurements for subjects. Among the 434 subjects, the daily blood glucose varied from 76.9 ± 11.3 to 144.2 ± 23.2 mg/dl. The 24-h MBG, PT140, and PT70 were 104 ± 10 mg/dl, 4.1 ± 5.8%, and 2.4 ± 5.3%, respectively. As for these parameters, no significant differences were found between men and women. The 95th percentile values were adopted as the upper limits of CGM parameters, which revealed 119 mg/dl (6.6 mmol/l) for 24-h MBG, 17.1% for PT140, and 11.7% for PT70. CONCLUSIONS: We recommend a 24-h MBG value <119 mg/dl, PT140 <17% (4 h), and PT70 <12% (3 h) as normal ranges for the Chinese population.